The Complexity of Constructing Evolutionary Trees Using Experiments - Brodal, Gerth Stølting; Fagerberg, Rolf; Pedersen, Christian N. S.; Östlin, Anna (BRICS Report Series, 2001)
We present tight upper and lower bounds for the problem of constructing evolutionary trees in the experiment model. We describe an algorithm which constructs an evolutionary tree of n species in time O(n d logd n) using at most n |d/2| (log2|d/2|−1 n + O(1)) experiments for d > 2, and at most n(log n + O(1)) experiments for d = 2, where d is the degree of the tree. This improves the previous best upper bound by a factor Theta(log d). For d = 2 the previously best algorithm with running time O(n log n) had a bound of 4n log n on the number of experiments. By an explicit adversary argument, we show an Omega(nd logd n) lower bound, matching our upper bounds and improving the previous best lower bound by a factor Theta(logd n). Central to our algorithm is the construction and maintenance of separator trees of small height. We present how to maintain separator trees with height log n + O(1) under the insertion of new nodes in amortized time O(log n). Part of our dynamic algorithm is an algorithm for computing a centroid tree in optimal time O(n). Keywords: Evolutionary trees, Experiment model, Separator trees, Centroid tree, Lower bounds